Trends of Temperature Extremes in China and their Relationship with Global Temperature Anomalies - 黄丹青 钱永甫 朱坚 (Advances in atmospheric sciences, 2010)
Changes of temperature extremes over China were evaluated using daily maximum and minimum temperature data from 591 stations for the period 1961-2002. A set of indices of warm extremes, cold extremes and daily temperature range （DTR） extremes was studied with a focus on trends. The results showed that the frequency of warm extremes （F WE） increased obviously in most parts of China, and the intensity of warm extremes （I WE） increased significantly in northern China. The opposite distribution was found in the frequency and intensity of cold extremes. The frequency of high DTR extremes was relatively uniform with that of intensity： an obvious increasing trend was located over western China and the east coast, while significant decreases occurred in central, southeastern and northeastern China; the opposite distribution was found for low DTR extreme days. Seasonal trends illustrated that both F WE and I WE showed signifi- cant increasing trends, especially over northeastern China and along the Yangtze Valley basin in spring and winter. A correlation technique was used to link extreme temperature anomalies over China with global temperature anomalies. Three key regions were identified, as follows： northeastern China and its coastal areas, the high-latitude regions above 40~0N, and southwestern China and the equatorial eastern Pacific.